Implication of active Erk in the classic type of human medulloblastoma - Wlodarski, Pawel K.; Boszczyk, Anna; Grajkowska, Wieslawa; Roszkowski, Marcin; Jozwiak, Jaroslaw (Folia Neuropathologica, 2008)
Molecular pathways underlying medulloblastoma (MB), the most common malignant brain tumour in children, are still under scrutiny. The mammalian target of the rapamycin (mTOR) pathway is one of the kinases that was recently found to be implicated in a number of human tumours. Also in the case of MB it is suspected that mTOR dysregulation may play an important role in pathogenesis. Active mTOR leads to translation of several proteins, some of which affect cellular proliferation. On the other hand, Akt/PKB (protein kinase B) and Erk (extracellular signal-regulated kinase, also called mitogen-activated protein kinase, MAPK) are two protein kinases whose hyperactivity leads to a number of downstream effects, including activation of mTOR. In our previous report we found that indeed Akt and Erk are variably activated in human MBs. However, because MBs are a highly heterogeneous group of tumours, we were unable to associate Akt or Erk activation with all the cases of MB. In this paper we evaluated six cases of MB, only of the classic subtype. We found that elements of the Erk pathway are hyperactive in all six tumours. Thus, we postulate that in classic type of MB, growth factor stimulation may lead to Erk upregulation and mTOR-dependent protein translation, causing malignant growth.